Wireless Network Design for Telecenter in Rural Area - Aboud, Satea Hikmat (2009)
Information and communication technology (ICT) employment and dissemination assists many countries in incorporating many goals of digital divide most importantly by opening telecenters in rural areas. Many telecenter projects have been implemented in Malaysia for example in the last ten years. Deployment of the projects usually, is subjected to so many problems due to inadequate infrastructure and appropriate design. This project aimed at the selection of an effective design of the network with a budget cost estimate, by using a system program which subsequently includes smart questions that would contribute to the solution. The research questions stated are: How to use the technology that fit telecenter project in rural areas? What is the estimated cost of the basic requirements for the design of network infrastructure and the deployment in this area? It was then found that Wi-Fi technology can be adopted as a viable technology in terms of cost for rural areas connectivity by connecting community centers to each other and to the Internet.